Assessment of the “weekend effect” in lower extremity vascular trauma - Jundoria, A; Grant, B; Olufajo, O; De La Cruz, E; Metcalfe, D; Williams, M; Cornwell, E; Hughes, K (Elsevier, 2019)
Background: Studies suggest that patients admitted on weekends may have worse outcomes as compared with those admitted on weekdays. Lower extremity vascular trauma (LEVT) often requires emergent surgical intervention and might be particularly sensitive to this “weekend effect.” The objective of this study was to determine if a weekend effect exists for LEVT.